Small public space vitality analysis and evaluation based on human trajectory modeling using video data. (November 2022) - Niu, Tong; Qing, Linbo; Han, Longmei; Long, Ying; Hou, Jingxuan; Li, Lindong; Tang, Wang; Teng, Qizhi
Abstract: Small public spaces are important for citizens to live and socialize with a high utilization rate. The vitality of small public space plays an important role in evaluating space quality and attraction and provides reference for urban governance issues such as vitality evaluation of public space, quality optimization, and site micro-renewal. Previous studies of vitality based on low-throughput surveys or big data with low positioning accuracy are not suitable for the high-efficiency study of small public space. In this study, a systematic framework of vitality quantification in small public spaces is built on fine-grained human trajectories extracted from videos for more efficient and refined human-oriented vitality evaluation. A multi-indicator vitality quantification method is first proposed to comprehensively represent human vitality, including number of people, duration of stay, motion speed, trajectory diversity and trajectory complexity. Furthermore, a video dataset of small public space along with our sub-index-assisted expert assessing scheme is proposed to evaluate our vitality quantification framework. Finally, we analyze the correlation between quantitative vitality indicators and the expert-assessing vitality through multiple linear regression and obtain the optimal vitality quantification model. The experimental results indicate that our dataset is reliable and the vitality quantification model constructed with our quantitative indicators can better characterize urban vitality than the previous model based on number of people and staying time. Highlights: A novel multi-indicator vitality quantification framework of small public space is proposed. A dataset along with an expert rating method is proposed for vitality quantification framework verification. The correlation between our indicators and overall vitality is analyzed and the effectiveness of our framework is verified.